PREPARING STUDENTS FOR MILITARY SPORTS ACTIVITIES IN PHYSICAL EDUCATION CLASSES IN THE SECONDARY EDUCATION SYSTEM - Erkaboyev Oybek Mukhammadjonovich (Web of Journals Publishing, 2024)
Military sports training of students is a direct preparation of young people for army life. Young men must come to the army physically and mentally prepared, then they will quickly adapt to army life. In sports, a young man, and then a young man, in addition to the opportunity to improve physically, also receives spiritual skills of courage, patience, overcoming oneself, which is so necessary in modern and often quite tough life.
Keywords: Physical culture, teens, basketball, handball, football, exercise, movement skills, skills-requirements, action games, physical qualities, endurance, military equipment, mental, moral, educational training.